The importance of human FcgammaRI in mediating protection to malaria. - Richard S McIntosh; Jianguo Shi; Richard M Jennings; Jonathan C Chappel; Tania F de Koning-Ward; Tim Smith; Judith Green; Marjolein van Egmond; Jeanette H W Leusen; Maria Lazarou; Jan van de Winkel; Tarran S Jones; et al. (PLoS Pathogens)
The success of passive immunization suggests that antibody-based therapies will be effective at controlling malaria. We describe the development of fully human antibodies specific for Plasmodium falciparum by antibody repertoire cloning from phage display libraries generated from immune Gambian adults. Although these novel reagents bind with strong affinity to malaria parasites, it remains unclear if in vitro assays are predictive of functional immunity in humans, due to the lack of suitable animal models permissive for P. falciparum. A potentially useful solution described herein allows the antimalarial efficacy of human antibodies to be determined using rodent malaria parasites transgenic for P. falciparum antigens in mice also transgenic for human Fc-receptors. These human IgG1s cured animals of an otherwise lethal malaria infection, and protection was crucially dependent on human FcgammaRI. This important finding documents the capacity of FcgammaRI to mediate potent antimalaria immunity and supports the development of FcgammaRI-directed therapy for human malaria.